ASTM international workshop on standards and measurements for tissue engineering scaffolds. Issue 5 (15th September 2014) - Simon, Carl G.; Yaszemski, Michael J.; Ratcliffe, Anthony; Tomlins, Paul; Luginbuehl, Reto; Tesk, John A.
Abstract The "Workshop on Standards & Measurements for Tissue Engineering Scaffolds" was held on May 21, 2013 in Indianapolis, IN, and was sponsored by the ASTM International (ASTM). The purpose of the workshop was to identify the highest priority items for future standards work for scaffolds used in the development and manufacture of tissue engineered medical products (TEMPs). Eighteen speakers and 78 attendees met to assess current scaffold standards and to prioritize needs for future standards. A key finding was that the ASTM TEMPs subcommittees (F04.41‐46) have many active "guide" documents for educational purposes, but few standard "test methods" or "practices." Overwhelmingly, the most clearly identified need was standards for measuring the structure of scaffolds, followed by standards for biological characterization, including in vitro testing, animal models and cell‐material interactions. The third most pressing need was to develop standards for assessing the mechanical properties of scaffolds. Additional needs included standards for assessing scaffold degradation, clinical outcomes with scaffolds, effects of sterilization on scaffolds, scaffold composition, and drug release from scaffolds. Discussions highlighted the need for additional scaffold reference materials and the need to use them for measurement traceability. Workshop participants emphasized the need to promote the use of standards in scaffold fabrication, characterization, and commercialization. Finally, participants noted that standards would be more broadly accepted if their impact in the TEMPs community could be quantified. Many scaffold standard needs have been identified and focus is turning to generating these standards to support the use of scaffolds in TEMPs. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 949–959, 2015.